Modelo de gestión administrativa - financiera para la imprenta ABC de la ciudad de Tulcán - Portilla Meneses, Yesenia Carolina (2016)
In all companies you can determine the great need for a model of financial administration hat serves the decision making regarding the economic and financial simuation. This research focuses on designing a management model where ABC Printing lacks a control tool which does not allow the owner to know the true income, expenses and costs incurred in a period of time determined therefore not known the income for the period. In addition you can identify that poor training, performance evaluation affects workers in production processes, resulting in delay in delivery of products. lt was detailed and everything related to the theoretical basis conceming the administrative and financial management was analyzed in order to support and to solve the problem, several important points as conceptualized: administrative management, financial management and profitability, which are relevant to the job research. two exemplary embodiments as qualitative and quantitative types of rescarch, empirical and theoretical methods, techniques and tools of research, which is vital because it allows acquiring results on the problem under study to give greater credibility was used in the description of the methodology - Through all the information collected is necessary to design management model that tend to follow the internal rules and extemal in which the company is governed, this will improve their competitive level and provides insight into the economic and financial situation and therefore the profitability of their company.